Edukasi Kesehatan Bagi Ibu Dan Calon Ibu Sebagai Upaya Pencegahan Masalah Stunting Di Desa Jatiadi Kecamatan Gending Kabupaten Probolinggo - Mutinda Teguh Widayanto (Abdi Panca Marga, 2019)
Government efforts to improve the level of public health need to be supported by all parties. The desire to create a superior generation can only be achieved if the community has a good degree of health. One of the problems in the health sector is still relatively high stunting in Indonesia. Stunting is the failure of a child to grow and develop optimally due to the impact of cumulative and ongoing nutritional deficiencies. Or chronic nutrition problems where families and the community do not feel that this is a problem, this is because not many people know the causes, impacts and prevention. The central and regional governments together are trying to overcome these problems. The Local Government of Probolinggo Regency also strives to solve this problem with various policies adopted. Panca Marga University Probolinggo Real Work Lecture (KKN) placed in Jatiadi Village, Gending District, Probolinggo Regency tried to participate in preventing stunting problems through Health Education activities for mothers and prospective mothers as an effort to prevent stunting problems in Teati Village, Gending District, Probolinggo Regency, which is intended for mothers who have toddlers and pregnant mothers. It is expected that with this activity the community's understanding of health can be increased and stunting sufferers can be reduced, so that the desire to realize a smart and superior healthy community can be achieved. Keywords: Stunting, Health Education, Pregnant Women, Toddler